2018
DOI: 10.1007/s10934-018-0556-9
|View full text |Cite
|
Sign up to set email alerts
|

Monodispersed mesoporous silica nanospheres based on pyridinium ionic liquids

Abstract: In the past decades, ionic liquids (ILs) have garnered a lot of attention especially in the field of green chemistry due to their unique properties which help to solve the problems posed by organic solvents. Interestingly, their applications are not limited to that only as ILs have the potential to become alternative templates in the development of mesoporous silica nanoparticles (MSNs). This work reported the usage of a series of pyridinium ILs as template in the synthesis of monodispersed mesoporous silica n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…It was observed that with both strategies, except for a minor change in the results, the size of the MSNPs decreased with increasing the length of HC, whereas the porosity and surface area of MSNPs increased in the same direction. This is shown by the reported results of C₁₈PyBr/C₁₂PyBr, for the mean particle size (nm), BET surface area (m 2 g⁻ 1 ) and pore volume (cm 3 g⁻ 1 ), respectively: 0.31, 5.63 and 3.57 [ 198 ]. The same authors employed experimental design to optimize the average surface area and particle size of the fabricated MSNPs and studied the loading and release of the drug quercetin (a flavonoid employed to prevent/treat some cancer types).…”
Section: Applications Of Il-based Surfactantsmentioning
confidence: 76%
See 2 more Smart Citations
“…It was observed that with both strategies, except for a minor change in the results, the size of the MSNPs decreased with increasing the length of HC, whereas the porosity and surface area of MSNPs increased in the same direction. This is shown by the reported results of C₁₈PyBr/C₁₂PyBr, for the mean particle size (nm), BET surface area (m 2 g⁻ 1 ) and pore volume (cm 3 g⁻ 1 ), respectively: 0.31, 5.63 and 3.57 [ 198 ]. The same authors employed experimental design to optimize the average surface area and particle size of the fabricated MSNPs and studied the loading and release of the drug quercetin (a flavonoid employed to prevent/treat some cancer types).…”
Section: Applications Of Il-based Surfactantsmentioning
confidence: 76%
“…ILBSs have been explored in various fields, including chemical synthesis and catalysis [ 165 , 166 , 167 , 168 , 169 , 170 ], drug delivery [ 171 , 172 , 173 , 174 , 175 , 176 , 177 ], biomass conversion [ 178 , 179 , 180 , 181 , 182 , 183 ], liquid crystal development [ 184 , 185 , 186 ], decontamination [ 187 , 188 , 189 , 190 , 191 , 192 , 193 ] and formation and stabilization of metal NPs [ 61 , 194 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 …”
Section: Applications Of Il-based Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…By changing the template from tannic acid to gallic acid, the particle size of synthesized MSNs increased from 240 nm to 600 nm [ 45 ]. Our research group also discovered that by increasing the alkyl chain length of the ionic liquid template, the particle size decreased [ 46 ]. The particle size of MSNs can also be controlled by utilizing grain growth suppressants.…”
Section: Fabrication Of Msnsmentioning
confidence: 99%
“… 2 Applications involving these systems range from polymers and polymer membranes 3 5 to the synthesis of porous materials. 6 , 7 Although ionic liquids possess several advantages such as low vapor pressure, low flammability, and a wide liquid range, 8 they may also present high expense, synthetic challenges, and non-negligible toxicity which may prevent their widespread use in industry. 9 …”
Section: Introductionmentioning
confidence: 99%